Music ethics and the community - Jahnichen, Gisa (Univesiti Putra Malaysia Press, 2015)
The topic Music Ethics and the Community is widely connected to all aspects of music. The contributors to this volume are from Malaysia, Indonesia, Australia, Thailand, Sri Lanka, Korea, Singapore, Brunei, Germany, Serbia and Iran. Questions of individual or communal ownership of traditions, ways of preservation and revival of specific performing arts, any perspective of the communal music market which is highly based on dynamic normative structures, questions of censorship and permissibility of music as well as related issues regarding the conduct and evaluation of music research and the use of music and sound in therapy fall under this broad topic.